Tylosin exposure reduces the susceptibility of Salmonella Typhimurium to florfenicol and tetracycline - Abraham Fikru Mechesso; Seung-Chun Park (BMC Veterinary Research, 2020)
Abstract Background Antibiotics exposure has been implicated in the emergence of bacterial strains that are resistant to structurally related or unrelated antibiotics. Tylosin is a macrolide antibiotic that has been administered to treat respiratory pathogenic bacteria in swine. Thus, this study was undertaken to evaluate the impact of exposure to a constant (3 μg/mL) and decreasing concentrations of tylosin on the susceptibility of Salmonella enterica serovar Typhimurium to various antibiotics. Results S. Typhimurium strains exposed to tylosin for 12 and 24 h in the in vitro dynamic model demonstrated at least an eight-fold increase in the minimum inhibitory concentrations (MICs) of florfenicol and tetracycline. Exposure to tylosin extended the lag-time of the growth curve and enhanced the generation of reactive oxygen species. Gene expression analysis demonstrated up-regulation of the acrAB and tolC Salmonella efflux pump genes and its global regulators (marA and soxS). Besides, the expression of ompC gene was down-regulated in tylosin exposed S. Typhimurium. Conclusion Exposure to decreasing concentrations of tylosin could reduce the susceptibility of S. Typhimurium to florfenicol and tetracycline.